MENCEGAH KORUPSI DI DAERAH DENGAN PENGAWALAN OLEH KEJATI - Florentinus Sudiran (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2017)
The aim of this research is to know,(1) The control of the high court in East Kalimantan province  on the multy years Contract projects with the sum Rp.2.38 trylion (2)  The team of the court is surely controlling the MYC projects  (3) If any difficulty the team will give legal opinion,(4) The team will involve the Inspectorate   here,(5) Both will meet once a month.The suggestions are (1)The team has to control in the field,(2) The meeting for both has to be reaalized , (3) Both are truly working together,(3) To do any way to avoid the corruption , (4) If any corruption has to be sentenced whoever ,(5) Both have to keep neutral anyway.